Bifunctional homologous alkali-metal artificial synapse with regenerative ability and mechanism imitation of voltage-gated ion channels. Issue 11 (31st August 2021) - Li, Lei; Hu, Luodan; Liu, Kai; Chang, Kuan-Chang; Zhang, Rui; Lin, Xinnan; Zhang, Shengdong; Huang, Pei; Liu, Heng-Jui; Kuo, Tzu-Peng
Abstract : The coexistence of digital and analog bifunctions emulating the two hemispheres of the brain, combined with versatile synaptic plasticity and regenerative ability, is achieved by lithium-incorporated bionic device based on artificial "ion channels". Abstract : As a key component responsible for information processing in the brain, the development of a bionic synapse possessing digital and analog bifunctionality is vital for the hardware implementation of a neuro-system. Here, inspired by the key role of sodium and potassium in synaptic transmission, the alkali metal element lithium (Li) belonging to the same family is adopted in designing a bifunctional artificial synapse. The incorporation of Li endows the electronic devices with versatile synaptic functions. An artificial neural network based on experimental data exhibits a high performance approaching near-ideal accuracy. In addition, the regenerative ability allows synaptic functional recovery through low-frequency stimuli to be emulated, facilitating the prevention of permanent damage due to intensive neural activities and ensuring the long-term stability of the entire neural system. What is more striking for an Li-based bionic synapse is that it can not only emulate a biological synapse at a behavioral level but realize mechanism emulation based on artificial voltage-gated "ion channels". Concurrent digital and analog features lead to versatile synaptic functions in Li-doped artificial synapses, which operate in a mode similar to the human brain with its two hemispheres excelling at processing imaginative and analytical information, respectively.